2023
DOI: 10.1002/advs.202301199
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Triboelectric Quasi‐Zero Stiffness Vibration Sensor with Ultrawide Frequency Response

Abstract: Sensors based on triboelectric nanogenerators (TENGs) have gained worldwide interest owing to their advantages of low cost and self‐powering. However, the detection of most triboelectric vibration sensors (TVS) is restricted to low frequency, whereas high‐frequency vibration signals are successfully measured in recent studies; their sensitivity still requires improvement. Hence, a highly sensitive vibration sensor based on TENG (HSVS‐TENG) with ultrawide frequency response is presented. This study is the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For the horizontal TENG, the optimal additional mass was 10 g due to the smaller vibration amplitude and smaller excitation acceleration in the horizontal direction. For the structural optimization of the TFTD-TENG, the balance between driving resistance force and mass is also very important …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the horizontal TENG, the optimal additional mass was 10 g due to the smaller vibration amplitude and smaller excitation acceleration in the horizontal direction. For the structural optimization of the TFTD-TENG, the balance between driving resistance force and mass is also very important …”
Section: Resultsmentioning
confidence: 99%
“…For the structural optimization of the TFTD-TENG, the balance between driving resistance force and mass is also very important. 58 Through optimization of each parameter, the output performance of the TFTD-TENG can be significantly improved. In the above structural optimization experiments, we only used the output voltage as the criterion, and the change law of I sc was consistent with the output voltage.…”
Section: Optimization Of Structural Parametersmentioning
confidence: 99%
“…Numerous studies have shown that TENG has become a versatile and efficient energy-harvesting and self-powered sensing technology with applications ranging from small-scale portable electronics to large-scale blue energy harvesting [ 30 , 31 , 32 , 33 , 34 ]. TENG has the advantages of low cost, light weight, simple structure, strong environmental compatibility, wide material selection, etc., showing obvious advantages in the field of self-powered vibration sensing technology [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In this paper, a vibration sensor based on ball TENG (B-TENG) was designed for marine pipelines condition monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…TENGs convert mechanical vibration into electrical energy based on triboelectrification and electrostatic induction, generating alternating current (AC) signals through repeated contact and separation of materials under the mechanical stimulus. One advantage of TENGs is that they can work with readily available mechanical energy, which is present everywhere. The majority of mechanical signals from the human body use to communicate, such as sound, body movements, and muscle contractions, could also be used in sensors or health monitoring devices with sensitive TENGs. Therefore, TENGs have been considered to be one of the most successful methods for extracting low-frequency mechanical energy for sensor development. By wearing a TENG device on the body respirator, cardiovascular and physical activity can be monitored.…”
Section: Introductionmentioning
confidence: 99%